Zulu - Baker, Stanley; Endfield, CY; Diamond Film Production ([United Kingdom] : Diamond Film Production, 2007)
This film set in Africa in 1879, recounts an incident following the epic battle of Isandhlawana. British soldier found themselves at a loss when confronted by a massive army of skillfully trained Zulu warriors-leading to what many historicans have cited as the most humaliating military defeat in recorded history
Acquisition for KPI (Kelab pencinta Ilmu)
Title from cover
Cast: Stanley Baker, Jack Hawkins, Ulla Jacobsson
Narration spoken : Richard Burton
VCD format
Keywords: Zulu War, 1879 -- Drama; Ethnology -- Africa -- Drama; Historical films; Africa -- Social life and customs -- Drama